2015
DOI: 10.1007/s10439-015-1252-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the Strength and Structure of Unruptured Cerebral Aneurysms

Abstract: Intracranial aneurysms are pathological enlargements of brain arteries that are believed to arise from progressive wall degeneration and remodeling. Earlier work using classical histological approaches identified variability in cerebral aneurysm mural content, ranging from layered walls with intact endothelium and aligned smooth muscle cells, to thin, hypocellular walls. Here, we take advantage of recent advances in multiphoton microscopy, to provide novel results for collagen fiber architecture in 15 human an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 37 publications
(49 reference statements)
4
81
0
Order By: Relevance
“…Mechanical tests of human aneurysm samples have suggested the stiffness of the wall may be associated to rupture 7 . It has also been shown that both wall structure and mechanical strength can vary from patient to patient even within the unruptured population, and that wall structure can also vary locally within the same aneurysm 23 . Furthermore, two subpopulations have been found in a study of unruptured aneurysms, one with weaker more vulnerable walls and another with stronger walls 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical tests of human aneurysm samples have suggested the stiffness of the wall may be associated to rupture 7 . It has also been shown that both wall structure and mechanical strength can vary from patient to patient even within the unruptured population, and that wall structure can also vary locally within the same aneurysm 23 . Furthermore, two subpopulations have been found in a study of unruptured aneurysms, one with weaker more vulnerable walls and another with stronger walls 23 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that both wall structure and mechanical strength can vary from patient to patient even within the unruptured population, and that wall structure can also vary locally within the same aneurysm 23 . Furthermore, two subpopulations have been found in a study of unruptured aneurysms, one with weaker more vulnerable walls and another with stronger walls 23 . Additionally, possible associations between global aneurysm hemodynamic characteristics and wall strength and stiffness have been identified 5 .…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, no biaxial mechanical data combined with the corresponding microstructure of both healthy (layer-specific) and aneurysmatic aortic tissues are yet available. To further increase the understanding and to improve rupture risk prediction it is necessary to study effects of localized wall changes (shown, for example, for cerebral aneurysms in [38]) by combining the microstructure with patient-specific mechanical data and systematically compare these changes with healthy abdominal aortic tissues. Such a knowledge can then be used to improve numerical models incorporating structurebased nonlinear material models, as was recently performed in [39] where the biaxial response of porcine aortic tissues was combined with the related microstructure identified using histological slices.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse flow conditions described above have been previously shown to be associated with aneurysm wall inflammation which itself is associated with aneurysm rupture 27 , wall weakening and stiffening characteristic of vulnerable walls 28, 29 , and damaged collagen architectures 30 . Additionally, these flow conditions have been associated with aneurysm rupture 31 .…”
Section: Discussionmentioning
confidence: 95%